ASSESSMENT OF GENETIC VARIABILITY FOR YIELD AND YIELD RELATED TRAITS IN WHEAT - GADDAM TARUN (The Journal of Research ANGRAU, 2025)
A field study was undertaken at Guru Kashi University, Talwandi Sabo in Bathinda (Punjab) throughout the Rabi season of 2023–2024 to evaluate the genetic variability of 43 wheat genotypes  for yield and yield associated characteristics. The experiment used a Randomized Block Design with three replications. Analysis of variance showed considerable variation in all traits except flag  leaf width, confirming significant genetic diversity among the genotypes. The maximum genotypic  and phenotypic coefficient of variation (GCV and PCV) were noted for each plant’s biological  yield (GCV: 36.03%, PCV: 39.86%), grain weight per spike (GCV: 29.78%, PCV: 30.18%), and  grains per spike (GCV: 22.01%, PCV: 22.23%), indicating their potential for selection. High heritability (>80%) combined with a high genetic advance (>30%)for grains per spike, expressed  as a percentage of the mean (heritability: 98.01%, genetic advance: 44.88%), grain weight per spike (heritability: 97.38%, genetic advance: 60.54%), and biological yield per plant (heritability: 81.71%, genetic advance: 67.09%), suggesting these characteristics were mostly controlled by additive genetic effects and could be effectively improved through selection. Traits such as days to flowering (heritability: 87.37%, genetic advance: 8.14%), days to maturity (heritability: 90.97%, genetic advance: 3.58%), and plant height (heritability: 72.87%, genetic advance: 12.77%) displayed high heritability with moderate genetic advance, indicating the impact of both additive  and non-additive gene effects.In contrast, traits like tillers per plant (heritability:17.57%) and flag  leaf area(heritability: 21.27%) showed low heritability and genetic advance, implying strong  environmental influence and limited potential for direct selection. This study found significant genetic variability within the wheat genotypes, with key yield-related traits showing strong potential  for genetic improvement.